Preminilary study on electronic number mapping in Malaysia - Yahya, Saadiah; Abu Samah, Syarul Emy (2008)
ENUM (Electronic Number Mapping) is a scheme for searching an address out of Internet resources by DNS retrieval in a form of URI which corresponds to a telecommunication number based on ITU-T E164 recommendation. ENUM Working Group was formed in 1999 by IETF.ENUM was standardized by introducing the basic protocol (RFC291) in 2000 which has been later improved (RFC3761) in 2004.With this protocol, ENUM will be extended to e- mail, facsimile on telephone line, web browsing etc.Currently, trials are done mainly in Europe, America and Asia, where Europe been the most active.Trials are also going on in main IT countries in Asia-Pasific region like Australia, Japan and South Korea. ENUM Working Group in Malaysia was formed sometime in 2003 but revived on 2007.Among the group duties are to perform various phases of ENUM and conduct future trials. Currently ENUM technology is still at its infant stage and not fully explored. This paper discusses the pos sible Malaysian implementation of ENUM, its challlenges and issues.